2005
DOI: 10.1097/01.olq.0000175403.68410.ec
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Douching, Condom Use, and Sexually Transmitted Infections Among Chinese Female Sex Workers

Abstract: Background and Objective-Vaginal douching has been hypothesized to increase a woman's risk for human immunodeficiency virus (HIV) infection. However, data on the prevalence of this practice and its association with condom use and sexually transmitted infections (STIs) are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 15 publications
6
37
2
1
Order By: Relevance
“…Open Journal of Obstetrics and Gynecology The mean age in our series was 28.4 years. It is identical to that of Desai [6] in India, which was 28.5 years and superior to those of Wang [10] in China, Cornier [5] in Bulgaria and Reed [11] in Indonesia which were respectively 23.5 years, 23.9 years and 25.8 years.…”
Section: Epidemiological Characteristics Of Womensupporting
confidence: 54%
See 2 more Smart Citations
“…Open Journal of Obstetrics and Gynecology The mean age in our series was 28.4 years. It is identical to that of Desai [6] in India, which was 28.5 years and superior to those of Wang [10] in China, Cornier [5] in Bulgaria and Reed [11] in Indonesia which were respectively 23.5 years, 23.9 years and 25.8 years.…”
Section: Epidemiological Characteristics Of Womensupporting
confidence: 54%
“…Our rate of 50.4% is higher than those of Reed [11] in Indonesia and Wang [10] in China, which were 39% and 41% respectively. Higher rates were reported by Nguyen [9] in Vietnam and Fonck [1] in Kenya, which were 75.9% and 94%, respectively.…”
Section: Prevalence Of Genital Infectionsmentioning
confidence: 63%
See 1 more Smart Citation
“…There was a strong association between decreased condom use and douching, and over a third of women believed that douching could help prevent STI. However, reviews of the impact of douching on health show the practice to be highly associated with pelvic inflammatory disease (PID) and significantly but less so with ectopic pregnancy and other adverse outcomes including bacterial vaginosis, chlamydia infection, cervical cancer, and higher rates of HIV transmission (40,41) although data on condom use and douching are contradictory in direction across studies.…”
Section: Sexually Transmissible Infectionsmentioning
confidence: 99%
“…Wang et al (40) examined the relationships between vaginal douching, STI and condom use among Chinese female sex workers and found that vaginal douching was associated with a doubled history of STI infection. There was a strong association between decreased condom use and douching, and over a third of women believed that douching could help prevent STI.…”
Section: Sexually Transmissible Infectionsmentioning
confidence: 99%